Anticancer of genus Syzygium: a systematic review - Mahmoud Dogara Abdulrahman; Harmand A. Hama (Open Exploration Publishing Inc., 2023)
Aim: One in eight fatalities globally are considered cancer-related. The need for cancer therapy is growing. Natural products continue to play a role in drug development, as up to 50% of authorized drugs in the last 30 years have been isolated from natural sources. Methods: Anticancer, antioxidant, antibacterial, antifungal, antiviral, analgesic, anti-inflammatory, and other actions have all been reported in research papers using plants from the Syzygium genus in the treatment and prevention of disease. Results: Results from the anticancer test showed that the genus, especially Syzygium aqueum, Syzygium samarangense, and Syzygium cumini had significant promise as an anticancer agent in vitro against several cancer cell lines. Numerous factors, including phytochemical composition, increased apoptotic activity, decreased cell proliferation, stopped angiogenesis, and reduced inflammation. Conclusions: These results, despite preliminary, show promise for further purification and investigation of bioactive compounds and extracts within the genus Syzygium for their anticancer properties.